Woodrow Wilson and the reimagining of Eastern Europe - Wolff, Larry 1957- (Stanford University Press, 2020)
Woodrow Wilson, the eastern question, and the end of the Ottoman Empire -- "This war of emancipation" : the Wilsonian deliverance of the "enslaved" Habsburg peoples -- Wilsonian friendship : personal sympathy and geopolitical transformation -- National majorities and national minorities in Wilsonian Eastern Europe -- Conclusion : the dynamics of Wilsonian mental mapping.